IS IT NECESSARY TO DRAFT A NEW OUTER SPACE TREATY FOR THE TWENTY-FIRST CENTURY? - Erices Bravo, Álvaro Andrés (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to describe and study the 1967 Space Treaty in the context of current space activities involving new subjects and objects of law. The document highlights the Treaty’s continued relevance due to its broad and general wording, which allows it to address a wide range of cases, while questioning the necessity of drafting a new Space Treaty for when mankind sets foot on Mars. Research methods: study of specialized bibliography and the Corpus Iuris Spatialis, and analysis of information related to space industry. In addition, the author conducted interviews with space law experts and professors Robin J. Frank, Frans G. von der Dunk, and Marta Gaggero Montaner, which are included in the Interview Appendix. Results: 1) Articles II, III, IV, V, VI, VII, VIII, IX, XI and XIII, are legal limitations to the principle of freedom of exploration and use enshrined in Article I of the 1967 Space Treaty; 2) Today, new terms and definitions are being developed not only within UNCOPUOS but also through the national space legislation of countries with space capabilities; 3) For mankind to set foot on Mars in a sustainable manner and establish permanent human and AI-operated settlements, the U.S. and the People’s Republic of China, current spacefaring superpowers, will need to adopt common and binding international rules applicable to all, for the greater good and the survival of our species. Discussion: is it realistic for us, as space lawyers, to consider the possibility of drafting a new Space Treaty for the twenty-first century? Does the classical characteristic of predictability of space law urge us to act?